Coping strategies for food insecurity among rural households: an observational study of adaptive mechanisms - Mbhenyane, Xikombiso; Makuse, Sefora; Tambe, Ayuk; Zuma, Mthokozisi (Frontiers in Sustainable Food Systems, 2025)
BackgroundDespite South Africa being food secure at the national level, overall food insecurity persists in rural communities with inadequate resources. The current study aims to investigate the state of food security and identify the coping strategies employed by households in response to food shortages within the rural communities.MethodsThe design was a cross-sectional descriptive survey. Two rural communities were purposefully selected; thereafter, household informants were conveniently selected. A researcher-administered validated questionnaire was used to collect data on demographic characteristics, food security and coping strategies from 280 households with 2,300 family members. Quantitative analysis was done using SPSS version 26.0.ResultsFood insecurity remains a major concern as 36.8% of households are still experiencing hunger and employed 25 strategies during periods of food shortages. The top adaptive strategies were reliance on inexpensive and culturally less favored foods (50.3%) and getting food from friends and relatives (40%).ConclusionFood insecurity was remarkably high; however, households devised coping strategies for survival. The development of interventions to eradicate hunger should remain a key commitment of decision-makers and be informed by the coping strategies.